Correlation of CoreValve implantation 'true cover index' with short and mid-term aortic regurgitation: A novel index. (15th November 2016) - Vavuranakis, Manolis; Kalogeras, Konstantinos; Lavda, Maria; Kolokathis, Michail-Aggelos; Papaioannou, Theodoros; Oikonomou, Euaggelos; Stasinopoulou, Mursini; Vrachatis, Dimitrios; Moldovan, Carmen; Kariori, Maria; Bei, Evelina; Vaina, Sophia; et al.
Abstract: Background: 'Cover index' has been proposed to appraise the congruence between the aortic annulus and the device, with the assumption of not taking into account the actual device implantation depth. The aim of this study was to investigate whether the annulus–prosthesis mismatch, as expressed with the new proposed 'true cover index' according to actual implantation depth, can predict aortic regurgitation (AR) after transcatheter aortic valve implantation (TAVI). Methods: Patients who had undergone TAVI with the self-expandable CoreValve device, were retrospectively studied. All available prosthesis sizes were ex-vivo scanned and the precise diameter at 0.3 mm intervals along each device was measured. The 'true cover index' was evaluated, as a ratio of the following: 100 × ([prosthesis actual diameter at implantation depth − annulus diameter] / prosthesis actual diameter at implantation depth). AR was echocardiographically evaluated at discharge and 30 days and classified as prominent if moderate, or trivial if none or mild. Results: Overall, 120 patients who had undergone TAVI, were considered eligible for the study. 'True cover index' was statistically significantly lower among patients with prominent AR in comparison with trivial AR at discharge (5.7 ± 4.8 mm vs 9 ± 5.1, p = 0.025), as well as at one month post-TAVI (5.4 ± 5.1 mm vs 9.0 ± 5.1, p = 0.023), indicating increased AR for smaller index. After adjustment for severe annulus calcification, impaired baseline LVEF and previous valvuloplasty, it remained an independent predictor of one month prominent AR (OR: 0.854, CI: 0.730–0.999; p = 0.048). 'True cover index' of < 4.3 was shown to predict one-month prominent AR with sensitivity = 75% and specificity = 82.5%. Conclusions: 'True cover index' is strongly and independently correlated with the short and mid-term AR after CoreValve implantation.